MANIPULATIVE WOMEN IN CHARLES DICKENS NOVEL GREAT EXPECTATIONS: MISS HAVISHAM, MRS JOE, ESTELLA - Bekmurodova Sevara Khasan kizi (American Journals Publishing, 2023)
This research paper discusses the portrayal of three female characters, Miss Havisham, Mrs Joe, and Estella, in Charles Dickens' novel, "Great Expectations," and their manipulative and powerful characteristics. The annotation notes that while Dickens depicted many female characters as victims of societal norms that constrained women in Victorian England, he also portrayed women who challenged patriarchal power structures. The paper cites various research papers that examine the motivations and reasons behind the manipulative behaviors of the female characters and explores how their actions reflect the social and cultural context of the Victorian era. The annotation highlights how the portrayal of these women raises questions about gender roles and societal expectations in the 19th century, and their impact on the lives of women.
Keywords: Charles Dickens, Great Expectations, female characters, gender relations, Victorian England, Miss Havisham, Mrs Joe, Estella, manipulation power dynamics.